Double knockin mice show NF-KB trajectories in immune signaling and aging - Rahman, Shah Md Toufiqur; Aqdas, Mohammad; Martin, Erik W.; Ardori, Francesco Tomassoni; Songkiatisak, Preeyaporn; Oh, Kyu-Seon; Uderhardt, Stefan; Yun, Sangwon; Claybourne, Quia C.; Mcdevitt, Ross A.; Greco, Valentina; Germain, Ronald N.; et al. (Cell Reports, 2022)
In vitro studies suggest that mapping the spatiotemporal complexity of nuclear factor KB (NF-KB) signaling is essential to understanding its function. The lack of tools to directly monitor NF-KB proteins in vivo has hin-dered such efforts. Here, we introduce reporter mice with the endogenous RelA (p65) or c-Rel labeled with distinct fluorescent proteins and a double knockin with both subunits labeled. Overcoming hurdles in simul-taneous live-cell imaging of RelA and c-Rel, we show that quantitative features of signaling reflect the identity of activating ligands, differ between primary and immortalized cells, and shift toward c-Rel in microglia from aged brains. RelA:c-Rel heterodimer is unexpectedly depleted in the nuclei of stimulated cells. Trajectories of subunit co-expression in immune lineages reveal a reduction at key cell maturation stages. These results demonstrate the power of these reporters in gaining deeper insights into NF-KB biology, with the spectral complementarity of the labeled NF-KB proteins enabling diverse applications.
CRIS-Team WoS Importer:2022-12-30